Meeting Report from the Genomic Standards Consortium (GSC) Workshops 6 and 7. Issue 1 (July 2009) - Field, Dawn; Sterk, Peter; Kyrpides, Nikos; Kottmann, Renzo; Glöckner, Frank; Hirschman, Lynette; Garrity, George; Wooley, John; Gilna, Paul
Abstract This report summarizes the proceedings of the 6th and 7th workshops of the Genomic Standards Consortium (GSC), held back-to-back in 2008. GSC 6 focused on furthering the activities of GSC working groups, GSC 7 focused on outreach to the wider community. GSC 6 was held October 10–14, 2008 at the European Bioinformatics Institute, Cambridge, United Kingdom and included a two-day workshop focused on the refinement of the Genomic Contextual Data Markup Language (GCDML). GSC 7 was held as the opening day of the International Congress on Metagenomics 2008 in San Diego California. Major achievements of these combined meetings included an agreement from the International Nucleotide Sequence Database Consortium (INSDC) to create a "MIGS" keyword for capturing "Minimum Information about a Genome Sequence" compliant information within INSDC (DDBJ/EMBL /Genbank) records, launch of GCDML 1.0, MIGS compliance of the first set of "Genomic Encyclopedia of Bacteria and Archaea " project genomes, approval of a proposal to extend MIGS to 16S rRNA sequences within a "Minimum Information about an Environmental Sequence", finalization of plans for the GSC eJournal, "Standards in Genomic Sciences " (SIGS), and the formation of a GSC Board. Subsequently, the GSC has been awarded a Research Co-ordination Network (RCN4GSC) grant from the National Science Foundation, held the first SIGS workshop and launched the journal. The GSC will also be hosting outreach workshops at both ISMB 2009 and PSB 2010 focused on "Metagenomics, Metadata and MetaAnalysis" (M3 ). Further information about the GSC and its range of activities can be found athttp://gensc.org, including videos of all the presentations at GSC 7.